Frailty and Parkinson’s disease: the role of diabetes mellitus - Komici, Klara; Pansini, Antonella; Bencivenga, Leonardo; Rengo, Giuseppe; Pagano, Gennaro; Guerra, Germano (Frontiers in Medicine, 2024)
PD is a chronic neurodegenerative disease associated to a progressive loss of dopaminergic neurons, clinically characterized by motor and non-motor signs. Frailty is clinical condition of increased vulnerability and negative health outcome due to loss of multiple physiological reserves. Chronic hyperglycemia and insulin resistance which characterize Diabetes Mellitus (DM), have been reported to alter dopaminergic activity, increase the risk of PD and influence the development of frailty. Even though diabetes may facilitate the development of frailty in patients with PD, this relationship is not established and a revision of the current knowledge is necessary. Furthermore, the synergy between DM, PD and frailty may drive clinical complexity, worse outcome and under-representation of these population in the research. In this review we aimed to discuss the role of diabetes on the development of frailty among patients with PD. We summarized the clinical characteristics and outcomes of patients with concomitant DM, PD and frailty. Finally, interventions to prevent frailty in this population are discussed.